Guanidinium and spermidinium decavanadates: as small biomimetic models to understand non-covalent interactions between decavanadate and arginine and lysine side chains in proteins - Paredes-Pérez, Luis F.; Mendoza, Angel; García-García, Amalia; Serrano-De la Rosa, Laura E.; Méndez-Rojas, Miguel A.; Melendez, Francisco J.; Castro, María Eugenia; González-Vergara, Enrique (Frontiers in Chemical Biology, 2024)
During the last three decades, numerous investigations have been conducted on polyoxidovanadates to treat several illnesses and inhibit enzymes. Numerous decavanadate compounds have been proposed as potential therapies for Diabetes mellitus, Cancer, and Alzheimer's disease. Only six relevant functional proteins interacting with decavanadate, V10, have been deposited in the PDB. These are acid phosphatase, tyrosine kinase, two ecto-nucleoside triphosphate diphosphohydrolases (NTPDases), the human transient receptor potential cation channel (TRPM4), and the human cell cycle protein CksHs1. The interaction sites in these proteins mainly consist of Arginine and Lysine, side chains binding to the decavanadate anion. To get further knowledge regarding non-covalent interactions of decavanadate in protein environments, guanidinium and spermidinium decavanadates were synthesized, crystallized, and subjected to analysis utilizing various techniques, including FTIR, Raman, 51 V-NMR, TGA, and X-ray diffraction. The DFT calculations were employed to calculate the interaction energy between the decavanadate anion and the organic counterions. Furthermore, the Quantum Theory of Atoms in Molecules (QTAIM) and Non-covalent Interaction-Reduced Density Gradient (NCI-RDG) analyses were conducted to understand the non-covalent interactions present in these adducts. Decavanadate can engage in electrostatic forces, van der Waals, and hydrogen bond interactions with guanidinium and spermidinium, as shown by their respective interaction energies. Both compounds were highly stabilized by strong hydrogen bond interactions N-H•••O and weak non-covalent interactions C-H•••O. In addition, the interactions between guanidinium and spermidinium cations and decavanadate anion form several stable rings. This study provides new information on non-covalent intermolecular interactions between decavanadate and small biomimetic models of arginine and lysine lateral chains in protein environments.